Empowerment of Handicraft Production and Marketing Activities at the Bunga Raya Waste Bank - Putra, Alfa Santoso Budiwidjojo; Kusumawati, Evi Dewi; Kartikasari, Dewi (PT Inovasi Pratama Internasional, 2023)
Waste management has become a significant challenge in modern times due to rapid population growth, urbanization, and changing lifestyles, resulting in a substantial increase in waste volume. One approach to address this issue is the establishment of waste banks. Bunga Raya Waste Bank, located in the RT. 03/RW. 11, Dusun I, Purbayan, Baki Subdistrict, Sukoharjo Regency, Central Java 57556, is an exemplary waste bank that plays a crucial role in waste management in the region. In addition to waste management, Bunga Raya Waste Bank has introduced empowerment programs through the production and marketing of handicrafts made from recycled materials. Economic empowerment through handicrafts production has the potential to offer a sustainable solution to reduce the negative environmental impact of waste while improving the livelihoods of the local community. Handicrafts made from recycled materials have shown great potential in creating local employment opportunities and supporting the community's economy. Moreover, they can serve as a tool to enhance environmental awareness and promote sustainable practices. However, to optimize this potential, a deep understanding of the challenges and opportunities faced by Bunga Raya Waste Bank in empowering handicraft production and marketing activities is required. In this context, this research aims to further investigate Bunga Raya Waste Bank's efforts in harnessing the potential of handicrafts made from recycled materials as a tool for community economic empowerment. We will analyze aspects such as the production process, marketing strategies, social and economic impacts, and challenges faced by this waste bank in implementing the program.